We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+2
1232
1
avatar+27664 

$${\mathtt{3}}{\mathtt{\,\times\,}}{{\mathtt{x}}}^{{\mathtt{2}}}{\mathtt{\,-\,}}{\mathtt{2}}{\mathtt{\,\times\,}}{\mathtt{x}}{\mathtt{\,-\,}}{\mathtt{5}} = {\mathtt{0}} = \left\{ \begin{array}{l}{\mathtt{x}} = {\frac{{\mathtt{5}}}{{\mathtt{3}}}}\\
{\mathtt{x}} = -{\mathtt{1}}\\
\end{array} \right\}$$

So alpha = 5/3 and beta = -1

To get the (quadratic) equation whose roots are alpha2 and beta2 we construct:

(x - alpha2)*(x-beta2) = 0   or:

 x2 -(alpha2+beta2)*x + alpha2*beta2 = 0

 

I'll leave you to put the numbers in.

 Apr 22, 2014
 #1
avatar+537 
-1

Wow Very Cmplex Math 

 Nov 3, 2017

22 Online Users